A delicate balance : portfolio analysis and management for intelligence information dissemination programs - Landree, Eric.; Silberglitt, R. S. (Richard S.); Chow, Brian G.; Sherry, Lance; Tseng, Michael S.; Rand eBooks (Santa Monica, CA : RAND, 2009)
This description of the application of the RAND Corporation's PortMan portfolio analysis and management method for the National Security Agency (NSA) Information Sharing Services (ISS) division demonstrates how PortMan (1) enables the data-driven analysis of project portfolios and (2) provides a means for monitoring the progress of potentially high-value projects and associated risk-mitigation strategies. RAND developed two sets of metrics to help ISS estimate the expected value of the projects in its portfolio, one for research and development (R&D) projects and one for operations and maintenance (O&M) projects. Metrics were based on elicitations of the important components of value and risk from ISS staff and an analysis of documents provided by ISS management. RAND also conducted a Delphi consensus-building exercise with subject matter experts from ISS's Senior Leadership Group (SLG) to estimate both the value and the probability of successful implementation of each project. PortMan allows for the inclusion of value, risk, and cost in the portfolio analysis, and RAND used a linear programming model to select a portfolio of projects that delivers the maximum portfolio expected value for the available budget. This analysis generated reproducible and auditable data to support programmatic decisionmaking within ISS; it also provided a venue in which ISS leadership could identify areas of consensus and non-consensus and debate the latter. Finally, it provided data and analysis of expected value versus program budget and expected value-to-cost ratios of individual projects that can be used by program managers and directors in discussions with supervisors and senior management.
Introduction: The Basics of Portfolio Management -- The RAND PortMan Method -- PortMan Evaluation of the NSA ISS Portfolio -- Conclusions -- Appendix A: Project Descriptions -- Appendix B: Research and Development Questions -- Appendix C: Operations and Maintenance Questions -- Appendix D: Delphi Exercise Results by Project and Question.
"RAND National Defense Research Institute."
Includes bibliographical references (p. 43-44).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- National Security Agency/Central Security Service; Intelligence service -- United States -- Management; Intelligence service -- United States; Program budgeting; Project management; Electronic books